A modified international prognostic index including pretreatment hemoglobin level for early stage extranodal natural killer/T cell lymphoma. Issue 11 (2nd November 2015) - Wang, Liang; Xia, Zhong-jun; Lu, Yue; Wang, Qiao-xuan; Niu, Shao-qing; Huang, Hui-qiang; Zhang, Yu-jing
Abstract : In this study, we investigated the prognostic role of pretreatment hemoglobin level in 321 patients with stage I/II extranodal natural killer (NK/T cell lymphoma (ENKTL). Patients with pretreatment hemoglobin level < 120 g/L had significantly inferior progression-free survival (PFS) and overall survival (OS) than those with hemoglobin level ≥ 120 g/L ( p < 0.05). In a multivariate Cox regression model, age, Eastern Cooperative Oncology Group (performance status), lactate dehydrogenase level, Ann Arbor stage and pretreatment hemoglobin level were all independent prognostic factors for PFS and OS ( p < 0.05). Using these five parameters, a modified international prognostic index (mIPI) model was constructed. This mIPI could categorize three groups with significantly different PFS and OS (both p < 0.0001) in both the training set and the validation set. In conclusion, this study confirmed the prognostic role of pretreatment hemoglobin level in ENKTL, and a newly modified IPI including pretreatment hemoglobin level could be used to further optimize treatments for patients with stage I/II ENKTL, especially in the era of asparaginase.